EVALUATION OF STENOSIS AFTER LAPAROSCOPIC URETEROLITHOTOMY - Andrea Putra, Aze; Wallad, Caesar Khairul; Umran, Amrizal; Hudaya, Syamsu; Hutasoit, Yonas Imanuel (Indonesian Urological Association, 2025)
Objective: This study aims to evaluate the probability of stenosis that occurs in the ureter due to the use of electrocautery during ureteral incision procedures in Laparoscopic ureterolithotomy (LU). Material & Methods: This study was conducted in Fatmawati Hospital Jakarta, we collected the data retrospectively in 22 patients diagnosed with ureteral stones who underwent LU procedure from 2014 to 2021, are eligible and have completed the follow-up protocol. The patient was evaluated by assessing the condition of the kidney after the procedure using ultrasound and CT scan to evaluate the presence of ureteral stenosis. Result: Ureteral stenosis was found in 6 of 22 patients (27.3%). Median follow-up time was 45 months (3-4 years). All of them were asymptomatic. Conclusion: There is a 27.3% chance patient will develop ureteral stenosis after LU. Though LU is one of the best methods for extracting large ureteral stone, the late complication after LU should be considered. Keywords: Electrocautery, laparoscopy ureterolithotomy, ureteral stenosis.